2021
DOI: 10.3390/ma14185396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Fume on Metakaolin Geopolymers’ Sulfuric Acid Resistance

Abstract: To demonstrate the importance of the Si/Al ratio in terms of geopolymer mix designs for acid resistance, a metakaolin-based geopolymer was modified by replacing the aforementioned precursor with different percentages of silica fume. Durability tests were performed by exposing geopolymers with varying amounts of silica fume (up to 9%) to sulfuric acid solution (pH 1) over a period of 84 days. Geopolymer samples were analyzed by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
(191 reference statements)
1
7
0
Order By: Relevance
“…The addition of microsilica to metakaolin-based AAMs at a substitution rate of ≥7.5 % was found to increase their resistance against sulfuric acid attack, presumably due to an increased Si/Al ratio of the resulting K-A-S-H gel, and because the presence of additional SiO 2 led (by some not yet understood reaction mechanism) to a densified silica gel in the corroded layer [23]. Possibly related to this observation is the finding that silica/sodium aluminate-based AAMs performed better in sulfuric acid corrosion testing when they were designed with excess silica (rice husk ash or microsilica) [16].…”
Section: Influence Of Aam Composition On Acid Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…The addition of microsilica to metakaolin-based AAMs at a substitution rate of ≥7.5 % was found to increase their resistance against sulfuric acid attack, presumably due to an increased Si/Al ratio of the resulting K-A-S-H gel, and because the presence of additional SiO 2 led (by some not yet understood reaction mechanism) to a densified silica gel in the corroded layer [23]. Possibly related to this observation is the finding that silica/sodium aluminate-based AAMs performed better in sulfuric acid corrosion testing when they were designed with excess silica (rice husk ash or microsilica) [16].…”
Section: Influence Of Aam Composition On Acid Resistancementioning
confidence: 98%
“…As mentioned in the previous Section, the corroded layer of AAMs is generally found to be depleted in Al, usually determined by spatially resolved chemical analysis [scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), electron probe microanalysis (EPMA) etc.]. In addition, several studies found that the X-ray diffraction (XRD) patterns of the corroded layer of low-Ca AAMs exhibits a broad hump centred at d ≈ 4.0 Å (2θ ≈ 22° for Cu Kα radiation), while the XRD patterns of the intact materials generally contain a broad hump centred at d ≈ 3.1 Å (2θ ≈ 29° for Cu Kα radiation) [16,18,22,23] (Fig. 2).…”
Section: Dealumination and Formation Of A Silica Layermentioning
confidence: 99%
“…In this study, we introduce a new class of electrode materials for the eCO2RR by electrocatalytically functionalizing a geopolymer (GP) material with Sn. GP is an inorganic amorphous aluminosilicate polymer made from e. g. metakaolin and alkali silicate precursors and is currently being in research focus as an alternative building material in construction industry [17–23] . GP can be used as a binder to substitute e. g., the established Portland cement (PC) in concrete and thereby inter alia drastically reduce CO 2 emissions of the CO 2 intensive construction sector, [24] while still maintaining the material‘s strength, durability, performance and cost.…”
Section: Introductionmentioning
confidence: 99%
“…GP is an inorganic amorphous aluminosilicate polymer made from e. g. metakaolin and alkali silicate precursors and is currently being in research focus as an alternative building material in construction industry. [17][18][19][20][21][22][23] GP can be used as a binder to substitute e. g., the established Portland cement (PC) in concrete and thereby inter alia drastically reduce CO 2 emissions of the CO 2 intensive construction sector, [24] while still maintaining the material's strength, durability, performance and cost. To produce GPbased concrete, metakaolin is mixed with other functional additives and can be poured as a fresh mortar with similar properties to self-compacting concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Another important property that characterizes these materials is their good resistance to acidic media. Several works have focused on the study of this phenomenon [ 11 , 49 , 50 , 51 , 52 , 53 , 54 ]. Although the experimental conditions varied from one study to another, in terms of the concentration of the etching solution used, the nature of the acids (HCl, H 2 SO 4 or acetic acid), the results showed that geopolymers are generally chemically stable with relatively low short-term mechanical strength losses.…”
Section: Introductionmentioning
confidence: 99%